Urban Migration in Imperial Germany: Towards a Quantitative Model - Hochstadt, Steve (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractMigration research has been dominated by broad assumptions which this paper brings into question. Modernization theory holds that rural-urban migration was one-way, permanent, and continually increasing during industrialization. Nominal-level research on urban populations tends to accept the idea that nonnatives are becoming permanent residents. Data from Germany show reality to have been quite different. Urban mobility peaked around 1900, and has fallen steadily since then. The great majority of urban inmigrants soon left the city, mainly returning to their rural origins. Thus a new model of urban migration is needed. This model must lake into account certain structural characteristics of urban migrants in Germany. Males were more mobile than females, but the differences lay primarily among unmarried adults, whose mobility rates were at least five times those of families. Mobility was inversely proportional to income: workers and domestics were several times as mobile as professionals and the self-employed. The paper does not construct a new model of migration but uses these data to raise questions which might lead to such a model.